Kewenangan Pemerintah Daerah dan Partisipasi Masyarakat dalam Pengelolaan Potensi Daerah - Farid, Mifta; Antikowati, Antikowati; Indrayati, Rosita (Lentera Hukum, 2017)
This article describes the relationship between the authority local governments and participation in the management of the potential of the region. The authors argue that local government has a broad authority within its jurisdiction to manage local potentials. One of the tasks borne by government is by following the country, namely hold some of the state as organization power, one of them is given to the public and private in publishing licensing. On one side, the role of the community is very important in the management of the potential of the region as a form of concern of the community development of area, then with the participation of the community hope to increase the income of the around and for the local government assets. On the other hand, residents as a their nets a an ongoing activity. Later in this article explain also forms of public participation in the management of the potential of the region. This article use the study literature regarding the authority local governments and the study legislation about the authority local governments that applies. The results of the study concluded that extent authority local governments one of which is the licensing on the management regional potential, on the other side, required public participation in the management of potential an area. Keywords: Local Government, Public Participation, Local Potentials